Оптимізація експериментальних параметрів та визначення експериментального значення критерію вебера струминно-щілинного гомогенізатора молока - Самойчук, Кирило Олегович; Самойчук, Кирилл Олегович; Samoichuk, Kyrylo; Ковальов, Олександр Олександрович; Ковалев, Александр Александрович; Kovalov, Oleksandr; Колодій, Олександр Сергійович; Колодий, Александр Сергеевич; Kolodii, Oleksandr; Сєрий, Ігор Олександрович; Серый, Игорь Александрович; Sieryi, Ihor (ТДАТУ, 2019)
UK: У статті представлено та проаналізовано результати оптимізації основних параметрів струминнощілинного гомогенізатора молока, за графіками, побудованими на основі даних, отриманих при проведенні експериментальних досліджень. Наведені результати оптимізації за показником жирності вершків, що використовуються при складанні нормалізованої суміші в залежності від ширини кільцевої щілини струминного диспергатора молока щілинного типу. RU: В статье представлены и проанализированы результаты оптимизации основных параметров струйно-щелевого гомогенизатора молока, построенных на основании данных, полученных в ходе экспериментальных исследований. Приведены результаты оптимизации жирности сливок, используемых при составлении нормализованной смеси, в зависимости от ширины кольцевой щели в струйном диспергаторе молока щелевого типа. EN: Reducing the energy costs of homogenization while ensuring the average diameter of fat globules at the level of technologically determined values (0.8-1.2 microns), is a priority for scientists in the industry. Prospective studies claim to reduce energy costs for the dispersing it is possible to achieve when using a jet homogenization, whose operation is based on creating the maximum difference between the velocity dispersion and the dispersed phase of the product, in particular design of of the jet–slot milk homogenizer type. The article presents and analyzes the results of optimization of the main parameters, based on the data obtained in the course of experimental studies. The results of optimization of the cream fat content used in the preparation of the normalized mixture, depending on the width of the annular slit in the jet milk disperser of the slit type are presented. The graph of optimization of the disperse phase speed depending on the cream fat content used in the experimental studies of the milk emulsion homogenization process is analyzed. The rational values of cream fat content, the width of the ring slit of the dispersant and the speed of the dispersed phase supply are presented and justified, using which the minimum energy costs are achieved while ensuring the average diameter of the fat globules at the level of technologically conditioned requirements (0.85 µm). On the basis of experimental data, the value of the Weber criterion, which is the main indicator determining the decrease in the average size of fat globules in the jet milk dispersant of the slit type, is determined. According to the results obtained, to reduce the energy costs of the dispersion process while ensuring the diameter of the fat globules at the level of technologically determined values, cream with a fat content of 40-42% should be used, which must be fed through an annular slot whose width is 0.5 mm at a speed of 11-13 m/s. The experimentally determined value of the Weber number for the jet-slot dispersant is 28 and confirms the results obtained in the study of the jet homogenizer of milk with a separate supply of cream
Оптимизация экспериментальных параметров и определение экспериментального значения критерия вебера струйно-щелевого гомогенизатора молока
Optimization of experimental parameters and identifying the experimental values of weber criterion in the slot type jet-mixing homogenizer of milk
Keywords: щілинний диспергатор; молоко; енергетичні витрати; середній діаметр кульок; вершки; жирова кулька; оптимізація